PENGEMBANGAN MULTIMEDIA INTERAKTIF PADA PEMBELAJARAN KIMIA MATERI STRUKTUR ATOM KELAS X MIPA: DEVELOPMENT OF INTERACTIVE MULTIMEDIA IN LEARNING CHEMISTRY ATOMIC STRUCTURE MATERIALS FOR HIGH SCHOOL - Vina Rachmawati; Sukarmin Sukarmin (FKIP University of Mataram, 2022)
This research aims to gain the feasibility of interactive multimedia on the chemical learning of atomic structure materials class X Mipa. This research is a study using research methods research and developmen, the research design used is a 4D model that is limited to 3 stages, namely define, design and develop. This studies became performed at SMAN 21 Surabaya on 33 college students of class X Mipa. This observe used validation instrument sheets, pretest and posttest, student response questionnaires and student observation questionnaires. If the price of the validation end result is ≥61% then it’s taken into consideration valid, the practicality price is ≥61% then it’s taken into consideration sensible and the effectiveness price is ≥61% then it’s taken into consideration effective. The validity of the contents and constructs of 85.6% and 82.92% falls into the class of very valid. Practicality obtained by 96.71% and 95.83% of student observations is considered practical. Effectiveness is obtained from the learning results of students using pretest and posttest questions and obtained pretest results of 21.21% and posttest results of 100% so that there is a difference between pretest and posttest students' grades. This suggests that interactive multimedia atomic structure materials can be used as a medium of chemical learning.Keywords: Interactive Multimedia, Atomic Structure, Chemistry